Consumption Smoothing Across States and Time: International Insurance vs. Foreign Loans - George M. von Furstenberg (Deutsche Bundesbank, 2004)
When countries, and macroeconomic models, open up to international capital markets, the welfare gains available through completion of financial markets for contingencies potentially are much greater than those available from access to noncontingent international borrowing. Intercasual insurance, reducing exposure to differences in contingent future cases, and not intertemporal smoothing between now and then is the big story in open economies although the two must be told together.
Keywords: F36; G22; E21; 330; Consumption Smoothing; International Economic Insurance; Arrow-Debreu Securities; Foreign Loans; International Risk Sharing; Versicherung; international; Internationale Anleihe; Gesamtwirtschaftlicher Konsum; Zeitpräferenz; Risiko; Wohlfahrtseffekt; Theorie; Schätzung; Welt; risk sharing